The effectiveness of POST-DISCHARGE telerehabilitation practices in COVID-19 patients: Tele-COVID study-randomized controlled trial - Esra Pehlivan; İsmail Palalı; Sibel Gayretli Atan; Demet Turan; Halit Çınarka; Erdoğan Çetinkaya (Annals of Thoracic Medicine, 2022)
AIMS: We aimed to investigate the effectiveness of a telerehabilitation exercise program performed without requiring any special equipment on the physical condition of COVID-19 subjects. SETTINGS AND DESIGN: This was a randomized controlled study. METHODS: This study included subjects with a history of hospitalization with a diagnosis of COVID-19 and discharged within 4 weeks. The subjects were divided into two groups randomly, namely telerehabilitation group (TeleGr, n = 17) or control group (CGr, n = 17). The TeleGr received breathing and range of motion exercises, active cycle of breathing technique, and an aerobic training 3 days a week for 6 weeks, while CGr received an exercise brochure with the same content. Subjects were evaluated using the modified Medical Research Council (mMRC) dyspnea score for dyspnea, 30 s sit-to-stand test (30STS) and short physical performance battery (SPPB) to determine their physical status, Saint George Respiratory Questionnaire (SGRQ) to assess quality of their life, and Beck Depression Inventory. All evaluations were carried out at home using videoconferencing. RESULTS: A significant improvement was observed in TelerGr in terms of mMRC (P= 0.035), 30STS (P= 0.005), 5 sit-to-stand time which is one of the subtests of SPPB (P = 0.039) and SGRQ scores. Significant improvement was observed only in the pain score in the CGr (P = 0.039). There was a statistically significant difference between the groups in SGRQ activity (P = 0.035) and total (P = 0.042) scores. In addition, more symptomatic improvement was found in TeleGr. CONCLUSION: Telerehabilitation exercise program with less technical equipment is a good alternative treatment method for COVID-19 subjects, which improves the quality of life and symptomatic status of subjects. Clinical Trial Registration Number: nct04402983